Prevalence And Risk for Fall Among Elderly in Urban Area of Southern Karnataka - Mahesh Venkatesha; Latha K; Varsha R Mokhasi; Muninarayana C; Ravishankar S; Lakshmi L (Medsci Publications, 2016)
Introduction: Falls in older adults are a significant cause of morbidity and mortality.  The cause is often multi-factorial, and may require a multi-disciplinary approach both to treat any injuries sustained and to prevent future falls. Objective was to estimate the prevalence of falls and risk factors for falls among elderly in an urban area. Methods: 90 elderly patients aged >60yrs were included randomly from urban area and data was collected using a pretested questionnaire. Physical examination and functional assessment was done. Results: In the study out of 90 elders, 42.2% of them reported falls in the previous year, of them 60.5% had one episode of fall and 39.5% them had recurrent fall. Most common reason for fall home was had uneven surfaces (60.5%). Abnormal Romberg's test was significantly associated with falls (p = 0.008). Mean ADL score was 19.66 ± 2.43 in elderly who had falls and 20.08 ± 2.09 in elderly who had no falls. Conclusions: Falls are very common among elderly and various risk factors present at house and with other comorbidities in the elderly it becomes important to prevent the falls by making necessary modifications.